Studi Etnobotani User-User (Semnostachya nigrescens Bremek) dari Ketambe, Aceh Tenggara: Skrining Fitokimia dan Aktivitas Antibakteri - Emma Sri Kuncari (The Ethnobiological Society of Indonesia, 2021)
User-User (Semnostachya nigrescens Bremek) is a member of the Acanthaceae tribe. This plant by the Ketambe society believed empirically contain bioactive compounds which is efficacious to treat wounds caused by scorpion bites (Scorpiones). Therefore, then phytochemical screening was carried out using the Cuilei method and antibacterial activity by agar diffusion method. The results showed that user-user contains several chemical compounds such as alkaloids, saponins, tannins, phenolic, flavonoids, steroids and glycosides. The antibacterial activity test showed that user-user methanol extract did not have antibacterial activity against Escherichia coli at concentrations of 500, 1000 and 1500 ppm.